SELECTED APPLICATIONS OF ROAD CHARGING IN URBAN AREAS - Ondrus, Jan; Palo, Jozef (Doprava a spoje, 2007)
There are several cities in the Europe e.g. London, Bristol, Rome, Oslo, Bergen or Stockholm that have established toll collection in their central parts. The main goal of toll implementation was particularly regulation of transport - to limit individual transportation demand and decrease congestions that are more and more frequently appearing in the centres. In other cities, the reason for introducing of toll collection was related with finance - to acquire financial resources for city communications network improvement, modernization of public mass transport or realization of important transportation project. In my contribution I would like to focus on several selected city toll collection systems in Europe from the point of view of technology, operational aspects and achievement of expected aims.